Webinar as a Form of E-Learning in Higher Education - S. D. Kalinina (Vestnik MGIMO-Universiteta, 2015)
Recently the major changes take place in the higher education. They relate to foreign and Russian universities. They are associated with the following trends: implementation of the concept of lifelong education, globalization of the educational space, change of educational paradigm, large-scale introduction of information and communication technologies in the educational process of universities. The article presents an overview of the main cases for the use of distance education technologies (DET) in the practice of the higher education. There are many examples, such as the introduction of systems for distance support of educational process (LMS - Learning Management System), use the MOOC - Massive Open Online Courses. The description of the characteristics of the webinar (a new form of training in a virtual educational environment of the University) is the focus of attention. The purpose of the webinar technology learning for the university teachers is improvement of information culture and competence formation of effective interaction with students in a rapidly changing environment of e-learning tools. This article describes the possibilities of webinar software technology platform that define the teacher tools, such as audio and video in real time, slide show presentations, use of virtual board, screen sharing of teacher desktop. It presents scenarios of webinar tools usage for online lectures and online seminars, technical and pedagogical preparation for them.